Shift in secretory profile of a pNET: from indolent glucagonoma to aggressive insulinoma – a case report - Gil dos Santos, Sara; Calheiros, Raquel; Oliveira, Joana; Santos, Ana Paula; Souteiro, Pedro (Frontiers in Endocrinology, 2026)
Pancreatic neuroendocrine tumors (pNETs) can change their hormonal profile over time, leading to new clinical syndromes that significantly impact prognosis and management. We report the case of a patient with a metastatic glucagon-secreting pNET who, after 14 years of disease and multiple treatment lines, developed insulin hypersecretion and severe, treatment-refractory hypoglycemia. Despite several strategies, including diazoxide, somatostatin analogues, glucocorticoids, everolimus, peptide receptor radionuclide therapy, and continuous glucose and glucagon infusions, glycemic control was not achieved, and the patient ultimately died from treatment complications. This case highlights the clinical challenges of managing metachronous hormonal syndromes and the importance of long-term endocrine follow-up in pNET patients. It also emphasizes the limitations of current therapeutic strategies and the urgent need for new treatment options, including alpha-emitting radiopharmaceuticals, which may offer improved disease and symptom control in advanced, insulin-secreting pNETs.